Crucible : Sigma Force #14 - Rollins, James, 1961-; Baskous, Christian (New York, NY : HarperAudio, 2019)
After his home is attacked and his pregnant girlfriend is kidnapped, Commander Gray Pierce and the Sigma Force confront deep spiritual mysteries tracing back to the Spanish Inquisition.
Read by Christian Baskous.
Keywords: Kidnapping -- Fiction; Pregnant women -- Crimes against -- Fiction; Suspense fiction; Science fiction; Audiobooks